2021
DOI: 10.1002/ajmg.b.32879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polygenic risk for suicide attempt and risky behavior on brain structure in young people with familial risk of bipolar disorder

Abstract: Bipolar disorder (BD) is associated with a 20-30-fold increased suicide risk compared to the general population. First-degree relatives of BD patients show inflated rates of psychopathology including suicidal behaviors. As reliable biomarkers of suicide attempts (SA) are lacking, we examined associations between suicide-related polygenic risk scores (PRSs)-a quantitative index of genomic risk-and variability in brain structures implicated in SA. Participants (n = 206; aged 12-30 years) were unrelated individua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 140 publications
(162 reference statements)
0
3
0
Order By: Relevance
“… 22 As reliable biomarkers of suicide attempts (SA) are lacking, Overs et al investigated the relationships between potential genetic and neuroimaging biomarkers of SA, found that SA-in-BD PRS and risky behavior PRS were negatively correlated with the volume of anterior cingulate structures on the lateral and caudal sides of the kiss, respectively, whereas both SA-in-MDD PRS and SA-in-BD PRS were positively correlated with measured cuneate volume. 23 This study demonstrates the correlation between PRS for suicide-related phenotypes and brain structural variations associated with SA. Future explorations of PRS, combined with a range of biological, phenotypic, environmental, and clinical data in high-risk populations, may provide valuable information for predictive models of suicidal behavior.…”
Section: The Phenotype Of Bd Based On Prsmentioning
confidence: 57%
“… 22 As reliable biomarkers of suicide attempts (SA) are lacking, Overs et al investigated the relationships between potential genetic and neuroimaging biomarkers of SA, found that SA-in-BD PRS and risky behavior PRS were negatively correlated with the volume of anterior cingulate structures on the lateral and caudal sides of the kiss, respectively, whereas both SA-in-MDD PRS and SA-in-BD PRS were positively correlated with measured cuneate volume. 23 This study demonstrates the correlation between PRS for suicide-related phenotypes and brain structural variations associated with SA. Future explorations of PRS, combined with a range of biological, phenotypic, environmental, and clinical data in high-risk populations, may provide valuable information for predictive models of suicidal behavior.…”
Section: The Phenotype Of Bd Based On Prsmentioning
confidence: 57%
“… 68 Some evidence suggests that individuals with or at risk for depression are associated with structural alterations in the cuneus. 69 71 Previous studies have reported that cuneus gray matter volume is associated with depression 72 and suicidal behavior 73 , 74 in MDD adults. Kim et al 75 found that MDD adolescents have a thinner cortical thickness in the cuneus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NSSI is a significant risk factor for suicide attempts and suicides ( 8 , 9 ). There is an approximately 30-fold higher suicide risk in patients with NSSI compared with the general population ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%